Graphene: Self‐Assembly of Graphene Oxide at Interfaces (Adv. Mater. 32/2014). (August 2014) - Shao, Jiao‐Jing; Lv, Wei; Yang, Quan‐Hong
<x xml:space="preserve">Abstract</x> As demonstrated by Q. H. Yang and co‐workers on page 5586, graphene oxide (GO), as a soft molecule, shows abundant self‐concentration phenomena at various interfaces due to its amphiphilic nature. The derived interfacial self‐assembly techniques starting with GO suspensions indicate an easily‐manipulated and "green" strategy for producing a variety of novel carbon nanostructures and finally carbon‐based functionalized materials with designed microstructures, textures, and functions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>